Strengthening Reading-written Processes in Early Childhood through Blended-learning - Jenny Zoraida Mora Reyes; Sandra Patricia Morales Rivera (Universidad Autónoma de Madrid, 2016)
In this innovation was intended to offer an alternative to meaningful work in an environment of classroom learning, strengthened through virtual space, better know as b-learning, which took place in an educational institution in Bogotá (Colombia), with preschool students or early childhood, whose objective was to strengthen their reading-writing skills, seeking development and approach to them. To do this, we designed and evaluated this innovation project with observational instruments and the recognition of previous skills against readiness in reading - writing activities, additional a family interview, instruments that allowed prove, empirically performed, the academic and motivational profit of this learning model in early childhood students, and additional to involve the family in the training process. Throughout the study we found that students in early childhood strengthened the processes of reading, writing and oral communication, and found difficulties with acces to computers, tutor commitment to the accompaniment, and presentation of at home work evidence from some students.